Desert ants learn vibration and magnetic landmarks. - Cornelia Buehlmann (Public Library of Science (PLoS), 2012)
The desert ants Cataglyphis navigate not only by path integration but also by using visual and olfactory landmarks to pinpoint the nest entrance. Here we show that Cataglyphis noda can additionally use magnetic and vibrational landmarks as nest-defining cues. The magnetic field may typically provide directional rather than positional information, and vibrational signals so far have been shown to be involved in social behavior. Thus it remains questionable if magnetic and vibration landmarks are usually provided by the ants' habitat as nest-defining cues. However, our results point to the flexibility of the ants' navigational system, which even makes use of cues that are probably most often sensed in a different context.